Implementation of Multicultural Education to Strengthen Religious Tolerance Character - Sulaiman, Sholehuddin; Musawir, Musawir; Aisda, Sufinatin (EDUCATIO : Journal of Education, 2023)
The implementation of multicultural education is a well-planned learning process that embraces the diversity of cultural backgrounds and societal norms. The character of Religious Tolerance Cooperation is an attitude of respecting differences in beliefs without considering others' backgrounds, all for a common goal. The objectives of this research are: 1) to understand the implementation of Multicultural Education in strengthening the character of Religious Tolerance at SMAN 1 Waru, Sidoarjo; 2) to comprehend and analyze the strengthening of the character of Religious Tolerance at SMAN 1 Waru, Sidoarjo; 3) to understand and analyze the supporting and inhibiting factors of the implementation of Multicultural Education in strengthening the character of Religious Tolerance at SMAN 1 Waru, Sidoarjo. This study adopts a qualitative descriptive approach, and the data collection methods include observation, interviews, and documentation. The data analysis technique is inductive and involves data reduction, data display, verification, and conclusion. The results of the implementation of Multicultural Education in strengthening the character of Religious Tolerance at SMAN 1 Waru, Sidoarjo are as follows: The school adopts the 2013 curriculum, and the methods used for multicultural education are contribution and enrichment. The implementation of Multicultural Education at SMAN 1 Waru, Sidoarjo includes having four religions represented at the school, namely Islam, Christianity, Catholicism, and Hinduism. The school provides teachers for each religion practiced by the students. The school follows the 5 S approach and engages in various activities such as extracurricular programs, OSIS (Student Council), and School Company. The results of strengthening the character of Religious Tolerance Cooperation are as follows: Teachers provide advice on multicultural education, instill values of mutual respect, appreciation, and acceptance of learning realities, support each other's religious celebrations despite different beliefs, and allow freedom to pray according to each individual's beliefs.